Linguistic Inclusivity in A Special Program in Foreign Language (SPFL) on Technology-Infused Teams-Games- Tournament (TGT): A Mixed-Method Study - Amie Rose J. Ampo (Researchparks Publishing, 2026)
This study investigated how a World Englishes (WE)–informed, technology- infused Teams-Games-Tournament (TGT) strategy enhanced linguistic inclusivity, learner engagement, and English achievement among SPFL students in a public secondary school in San Pedro, Laguna. This study, conducted during the School Year 2025-2026, utilized a convergent parallel mixed-methods design in which quantitative data were gathered from 220 students through pre-tests, post-tests, and surveys. At the same time, the qualitative data were obtained from semi- structured interviews, focus groups discussions, and classroom observations. Findings showed a marked improvement in performance, with mean scores rising from Least Mastered (M = 6.46) to Mastered (M = 43.52) after the intervention. Surveys indicated very high engagement and acceptance of diverse English varieties, while qualitative results highlighted increased linguistic confidence, reduced anxiety in using localized English, and stronger participation supported by digital tools and team-based activities. Teachers affirmed that integrating WE principles with technology-enhanced TGT validated learners’ linguistic identities and fostered inclusive, culturally responsive classroom environments. The study also produced an approved School Learning Action Cell (SLAC) session plan as its official output, supporting sustained professional development and the institutionalization of WE-informed,`technology-supported pedagogy. Overall, the study demonstrated that combining WE perspectives with a tech-supported TGT model is an effective, context-appropriate approach to improving language learning in multilingual Filipino settings. Its results align with SDG 4, Ambisyon Natin 2040, and NIBRA, contributing evidence-based insights for equitable and culturally grounded English language education in the Philippines.